The effects of diatom pore-size on the structures and extensibilities of single mucilage molecules. (7th August 2017) - Sanka, Immanuel; Suyono, Eko Agus; Alam, Parvez
Abstract: Diatoms secrete extracellular polymeric substances (EPS), or mucilage, around the cell wall that may serve to aid in motility and form a discrete layer that may help maintain thicker layers of EPS that have a greater role in adhesion. Mucilage molecules adhere to the diatom frustules, which are biosilica skeletons that develop from the diatom cell walls. Here, molecular dynamics methods were used to determine the characteristics of mucilage molecules as a function of pore size; notably 1, 4- α -D-galacturonic acid, 1, 4- β -glucuronic acid and 1, 4- β -D-mannuronic acid. These uronic acids differ from each other in structure and extensibility as a function of their folding characteristics. Here, we find that when overlain upon a pore, mucilage molecules try to return to their native folded states but are restrained by their interactions with the silica surfaces. Furthermore, the extensibility of mucilage molecules over pore spaces affects the extent of mechanical energy required to straighten them. As such, different EPS molecules will affect sliding, friction and adhesion to subsequent layers of EPS in different ways. We conclude that higher EPS extensibility is homonymous with higher adhesive or frictive resistance since the molecules will be able to strain more before they reach the most extended (and thus rigid) conformation. The research herein is applicable to modern engineering as it yields insight into the biomimetic design of molecules and surfaces for improved adhesion or motility. Graphical abstract: Highlights: Diatom mucilage modelled as single molecules over porous biosilica. Beyond certain pore sizes mucilage molecules have greater ability to fold towards their native states. Greater extents of folding permit greater molecular extensibility and thus greater mobility for attachment. Specific biopolymers fold dramatically and are thus more extensible and well-attached biofouling molecules over pores.